Left ventricular assist device bioinformatics identify possible hubgenes and regulatory networks involved in the myocardium of patients with left ventricular assist device - Ajmal, Maryam; Ajmal, Aisha; Rizvi, Maryam; Salim, Umar; Huang, Lei (Frontiers in Cardiovascular Medicine, 2022)
Objective The aim of this study was to clarify the changes of myocardial gene expression profile after left ventricular assist device (LVAD) implantation and the related molecular biological significance. Methods A thorough bioinformatic analysis to evaluate the changes in gene expression profile in patients pre-LVAD and post-LVAD was conducted. Four relevant gene expression datasets — GSE430, GSE974, GSE21610 and GSE52601 from Gene Expression Omnibus database were downloaded. Analysis of GEO2R, Gene Ontology, protein-protein interaction were used to determine differentially expressed genes (DEGs) and their function, respectively. Results A total of 37 DEGs were identified, including 26 down-regulated and 11 up-regulated genes. The molecular function of DEGs were enriched in “cytokine activity”, “neurotransmitter binding”, “receptor ligand activity”. The gene set enrichment analysis revealed an overall marked increase of neutrophil degranulation signalling, closely correlated with the G protein coupled receptor (GPCR) — ligand binding process after LVAD assistance. 16 hubgenes in these DEGs were further selected and the biological process involved is mainly related to positive regulation of leukocyte chemotaxis mediated by chemokines. Conclusion Inflammatory signalling pathway is crucial for the pathophysiology after LVAD implantation. Chemokines mediate cardiac inflammatory response and tissue remodelling after LVAD implantation through G protein coupled receptor - ligand binding.